TuMV management for brassica crops through host resistance: retrospect and prospects. (23rd April 2019) - Li, G.; Lv, H.; Zhang, S.; Zhang, S.; Li, F.; Zhang, H.; Qian, W.; Fang, Z.; Sun, R.
Abstract : Turnip mosaic virus (TuMV), the only potyvirus known to infect brassicas, is a devastating virus threatening many economically important brassica crops, including cabbage, Chinese cabbage, oilseed rape and mustard. TuMV disease, which was first discovered in the United States, is now found worldwide, especially in Europe, Asia and North America. TuMV results in a yield loss of up to 70% and has a wide host range, infecting most cruciferous plants, as well as many non‐cruciferous species. This virus is also characterized by high pathotype diversity because of its highly variable genome structure and has been divided into 12 pathotypes. These characteristics, as well as its nonpersistent transmission mode by as many as 89 aphid species, mean the disease is difficult to prevent through traditional methods such as the application of chemicals, prompting researchers to seek host resistance for effective control. During the last decade, extensive studies have been conducted to investigate inheritance, mapping and cloning of the TuMV resistance genes, and several NB‐LRR‐ or eIF‐encoding loci with divergent molecular mechanisms have been uncovered. These studies have greatly facilitated resistance breeding for brassica crops and have advanced our understanding of virus−host interactions.